2001
DOI: 10.1081/wct-100102655
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS OF OXIDATIVE DEGRADATION OF CARBOHYDRATES DURING OXYGEN DELIGNIFICATION. II. REACTION OF PHOTOCHEMICALLY GENERATED HYDROXYL RADICALS WITH METHYL Β-Cellobioside

Abstract: Reactions involving methyl b-cellobioside and several oxygen species were used to investigate cleavage of glycosidic linkages in cellulose by reaction with photochemical hydroxyl radicals. The intent is not to reproduce delignification conditions, but rather to study the specific behavior of carbohydrate models toward hydroxyl radical. Experiments show that hydroxyl radicals are responsible for the degradation of glycosidic linkages in methyl b-cellobioside by substitution reactions displacing cellobiose, D-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 8 publications
1
32
0
2
Order By: Relevance
“…This suggests that the higher hemicellulose content might be a factor for the slightly higher viscosity for OO-conventional pulp at the same Kn in comparison with OPxOPxO-pulp, as they serve to protect cellulose from harmful free hydroxyl radicals that are continuously generated during oxygen delignification. (Guay et al 2002;Violette and van Heiningen 2002;van Heiningen and Violette 2003).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the higher hemicellulose content might be a factor for the slightly higher viscosity for OO-conventional pulp at the same Kn in comparison with OPxOPxO-pulp, as they serve to protect cellulose from harmful free hydroxyl radicals that are continuously generated during oxygen delignification. (Guay et al 2002;Violette and van Heiningen 2002;van Heiningen and Violette 2003).…”
Section: Resultsmentioning
confidence: 99%
“…This was because more lignin was degraded by more HO· generated by the Fenton's reaction system. Meanwhile, the rate of viscosity reduction also increased with the amount of HO· because of the poor reaction selectivity of HO·, which could not only react with lignin but also degrade carbohydrates Reitberger et al 2001;Guay et al 2000Guay et al , 2001. The selectivity of delignification was 1.8 when 10 mL of H 2 O 2 were added into the reaction system, but the selectivity of delignification dropped to 1.2 when the amount of H 2 O 2 increased to 40 mL.…”
Section: Reaction Of Ho· With Emcc Bamboo Pulpmentioning
confidence: 95%
“…HOO·, O 2 · -, HO· and so on, which are mainly generated from reactions between phenolic units in lignin and molecular oxygen during the process (Ericsson et al 1971;Gierer and Imsgard 1977;Gratzl 1992;Yokoyama et al 1996). Studies have shown that these active oxygen species, especially HO·, attack not only lignin, but also carbohydrates, resulting in lower pulp strength and yield (Guay et al 2000(Guay et al , 2001. To further understand the underlying fundamental chemistry in oxygen delignification in order to improve the selectivity of delignification, the mechanisms of oxidative degradation of carbohydrates and lignin have been investigated (Konishi et al 2009;Nakagawa et al 2012;Yokoyama et al 2011;Kalliola et al 2011;Rovio et al 2011;Kuitunen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism for the Fenton depolymerization of the dissolved cellulose presumably is that the hydroxyl radical that comes from the Fenton reaction cleaves the -1,4-linked bond. The hydroxyl radical attack takes place at the anomeric carbon, and can readily break down any encountered glycosidic linkage in cellulose (Guay et al 2002). However, besides cleaving glycosidic linkages, other reactions between hydroxyl radical and cellulose would also take place, especially for very low DP.…”
Section: Mechanism For Fenton Depolymerization Of Cellulose Dissolvedmentioning
confidence: 99%